The Role of Tourism Sector on Central Java Economy - Sotya Fevriera; Agatta Shelly Septya Agni (Universitas Negeri Malang, 2025)
The purpose of this research is to analyze the effect of the tourism sector on the economy of Central Java province. The analysis method is a random effect model (REM) which is estimated using data from 35 regencies/cities in Central Java during some periods between 2001 and 2023. The result shows that the number of tourists, number of tourism objects, number of lodgings, number of restaurants, and number of workers on the tourist object, each has a positive significant effect on the real GRDP. Moreover, this research also found that there is a random effect on the regression coefficient of the number of tourists, number of tourism objects, and number of lodgings among regencies/cities in Central Java.